Derivatives of 5-hydroxynicotinic Acid: New Compounds with Cardioprotective Action - Danilenko, Lyudmila M. (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: The search for new compounds with cardioprotective activity among the derivatives of 5-hydroxynicotinic acid is promising. Objectives: The objective of this study is to study the cardioprotective effects of the derivatives from 5-hydroxynicotinic acid SSC-77 (K-5-hydroxynicotinic acid) and SSC-497 (Mg-5-hydroxynicotinica acid). Methods: The cardioprotective effect of SSC-77 and SSC-prisocorubicin (20 mg/kg, intraperitoneally for 48 h) pathology was assessed by the results of the functional test with high-frequency stimulation (480 bpm). The research of myocardial resistance to ischemia/reperfusion injury was studied according to hypo-reperfusion model on an isolated rat heart on the record of pressure in the left ventricle. The isoenzyme creatine phosphokinase (KFK-MB) and lactate dehydrogenase (LDH) were determined for the complex evaluation of myocardial damage in the flowing off perfusate from isolated hearts. The activity of lipid peroxidation (LPO) was assessed by the content of malondialdehyde (MDA) and diene conjugates (DC). Results: SSC-77 (27.6 mg/kg/day) and SSC-497 (58.1 mg/kg/day) show a cardioprotective effect using the doxorubicin pathology model, which is expressed in the decrease of diastolic dysfunction coefficient (StТTI) to 2.1 ± 0.2 r.u. and 3.3 ± 0.1 r. units, respectively, as compared with the control group 8.3 ± 0.1 r. un. Using the model of hypo-reperfusion, the substances SSC-77 (10−6 mol/l) and SSC-497 (10−6 mol/l) prevent the decrease of contractility indices on the 5th and 20th min during the reperfusion period in comparison with the control where the fall made 50%. The cardioprotective effect was confirmed by 47% and 39% decrease concerning the levels of KFK-MB marker damage by 39% and 47% and LDH by 21.8% and 19.6%, respectively, in the series with SSC-77 and SSC-497 in comparison with the control group, as well as by the prevention of LPO products MDA and DC accumulation in the ventricular myocardium. Conclusion: The derivatives of 5-hydroxynicotinic acid SSC-77 and SSC-497 reduce diastolic dysfunction, prevent the decrease of cardiac functional activity after ischemia/reperfusion, reduce the irreversible damage of cardiomyocytes, and have antioxidant properties